Homeschooling: Answering the Challenges of Alternative and Innovative Education - Malik, Halim K (Universitas Negeri Padang, 2025)
Homeschooling as an alternative form of education is growing and gaining popularity worldwide, particularly in response to the changing needs of modern society, which demands a more personalized, flexible, and individual-centered education. This paper will discuss and explore homeschooling as an innovative solution that offers a more adaptive learning approach, allowing students to learn at their own pace and according to their interests. Through this model, families can create a safe, supportive, and enriching learning environment, which is crucial for developing students' character and social skills. Furthermore, homeschooling allows for the use of increasingly sophisticated digital learning technologies and resources, expanding the scope and quality of learning beyond the traditional classroom. The final section of the paper will provide an alternative curriculum deemed appropriate to these needs. The advantages and challenges faced in implementing a homeschool curriculum will be outlined, as well as its relevance in the context of future education that is more oriented towards personal development and student needs. Furthermore, digital educational technologies and resources will further enhance the effectiveness of homeschooling as an innovative educational alternative.